Annealing effects on electrical and optical properties of a-Si:H layer deposited by PECVD. (December 2015) - Elghoul, N.; Kraiem, S.; Jemai, R.; Zebentout, B.; Khirouni, K.
Abstract: We report the optical and electrical properties of hydrogenated amorphous silicon (a-Si:H) layer doped with boron, before and after thermal annealing at different temperatures. It is found that the optical band gap increases from 1.44 eV for samples without annealing to 2.3 eV for samples annealed at 800 °C. Also, thermal annealing decreases the conductivity activation energy from 0.218 eV to 0.048 eV. These results show that thermal annealing can efficiently activate the dopants in films. The electrical properties of the obtained Schottky barrier diodes (SBDs) such as ideality factor n, series resistance R s and barrier height ϕ bo were extracted from I – V curves using Cheung׳s method. The ( I – V ) analysis based on thermionic emission (TE) theory shows a decrease of the barrier height and an increase of the ideality factor when the temperature decreases. These anomalies are explained with a double Gaussian distribution of the barrier heights due to the barrier height inhomogeneities at the metal–semiconductor interface.